2000
DOI: 10.1086/313910
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Meningitis in Malawian Adults: Pneumococcal Disease is Common, Severe, and Seasonal

Abstract: We prospectively collected laboratory details and outcome data on all patients with laboratory-confirmed cases of meningitis that presented to our unit in Blantyre, Malawi, from 1 April 1998 through 31 March 1999. There were 502 patients with cases of meningitis; the most common causative organisms were Cryptococcus neoformans and Streptococcus pneumoniae. This pattern probably reflects the local human immunodeficiency virus (HIV) seroprevalence (31%) and is different from the pattern in 1974, when Neisseria m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 16 publications
7
81
3
Order By: Relevance
“…We did not isolate Neisseria meningitidis in this study; that could be explained by the fact that, bacteria are mainly involved in the cases of epidemics of meningitis in sahelian region of Cameroon. C. neoformans was the only microbe responsible of fungal meningitis, and in 40% of the cases of meningeal irritation syndrome from patients with AIDS; these results are in accordance with those of previous studies (Gordon et al, 2000;Roos, 2003;Millogo et al, 2004;Békondi et al, 2006), since Cryptococcal meningitis has been described as the most common life-threatening opportunistic fungal infection in patients with immune-compromised status.…”
Section: Discussionsupporting
confidence: 91%
“…We did not isolate Neisseria meningitidis in this study; that could be explained by the fact that, bacteria are mainly involved in the cases of epidemics of meningitis in sahelian region of Cameroon. C. neoformans was the only microbe responsible of fungal meningitis, and in 40% of the cases of meningeal irritation syndrome from patients with AIDS; these results are in accordance with those of previous studies (Gordon et al, 2000;Roos, 2003;Millogo et al, 2004;Békondi et al, 2006), since Cryptococcal meningitis has been described as the most common life-threatening opportunistic fungal infection in patients with immune-compromised status.…”
Section: Discussionsupporting
confidence: 91%
“…Highly active antiretroviral therapy (HAART) reduces this risk but leaves it 35 times higher than that for meningitis patients without HIV infection (34,130,143). The increased risk of pneumococcal infections of HIV-infected patients has a profound impact in low-resource countries, where up to 95% of patients with pneumococcal meningitis have been reported to be HIV positive (128,129,176,198,213). The clinical presentations of HIV-positive and HIV-negative patients with bacterial meningitis are similar (198,213), although one study reported a higher seizure rate among HIV-positive patients (236).…”
Section: Immunocompromised Statementioning
confidence: 99%
“…Although cases of cryptococcosis in AIDS patients have decreased in developed countries due to the introduction of highly active antiretroviral therapy in the mid1990s, this disease remains responsible for up to 30% of the attributable mortality in AIDS patients in regions where highly active antiretroviral therapy is not readily available, such as Southeast Asia and Africa (7,9,12,24,25,27,28,37).…”
mentioning
confidence: 99%